Sensory Data and Performance Practice in Blue Raincoat’s 2015 Production of W. B. Yeats’s On Baile’s Strand (1904) - Trench, Rhona (Hungarian Journal of English and American Studies, 2020)
From the topography of dolmens, cairns, passage tombs, sea cliffs, holy wells, and lakes of County Sligo, Yeats’s narratives continued to be strongly inspired by “the waters and the wild” of its landscape. In 2015, Sligo’s resident professional theatre company, Blue Raincoat, staged a series of events entitled “A Country Under Wave” honoring the celebration of the poet-playwright’s 150th birthday. This paper examines their production of On Baile’s Strand (1904) on Streedagh Beach in June 2015, which opened “A Country Under Wave,” and explores the ways in which the specific features of the location were key to ensuring that this ritual drama could play effectively because it penetrated its surroundings in different ways. Special attention is paid to examining how we might perceive and understand a performance in the outdoors without a designed stage, lighting, and technologically designed sounds. (RT)